2015
DOI: 10.7314/apjcp.2015.16.2.635
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Delayed Diagnosis of Cervical Cancer in Iran - a Survey in Isfahan City

Abstract: Recently the concept of delayed diagnosis has become as an important issue in the cancer prevention and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
7
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
3
19
7
2
Order By: Relevance
“…There was evidence that regular visits to medical practitioners, including attendance for routine screening, were associated with shorter delay in patients with gynecological cancers [28]. A study conducted in Iran by Behnamfar and Azadehrah found that history of pap smear had significant association with delay at presentation [29], even though our findings did not demonstrate this association.…”
Section: Discussioncontrasting
confidence: 77%
“…There was evidence that regular visits to medical practitioners, including attendance for routine screening, were associated with shorter delay in patients with gynecological cancers [28]. A study conducted in Iran by Behnamfar and Azadehrah found that history of pap smear had significant association with delay at presentation [29], even though our findings did not demonstrate this association.…”
Section: Discussioncontrasting
confidence: 77%
“…Similar studies conducted in Sudan [50] and Nigeria [51] reported that up to 72% and 86% respectively of the women with cervical cancer were diagnosed at an advanced stage (FIGO stage III and IV). Our study findings were also lower than the Nepal and Iran studies that reported study that reported 80.9% [52] and 89.1% [53] respectively. According to Mlange et al [54], these differences could be explained by geographical variability and social economic status which could hinder the accessibility to health care facilities and probably poor health seeking behaviour.…”
Section: Discussioncontrasting
confidence: 92%
“…However, in Iran the number of women seeking for screening is limited due to the limited screening programs and lack of information about such programs. Hence, most cases with cervical cancer are detected at late stages (Rouhollahi et al, 2014;Behnamfar and Azadehrah, 2015). Cervical cancer preventive programs can be effective in increasing cervical cancer knowledge, perceived susceptibility, and cancer prevention behavior (Choi, 2013).…”
Section: Investigation Of the Role Of Training Health Volunteers Inmentioning
confidence: 99%
“…programs, such as Pap smear test, play an important role in early detection, or prevention or delay in progression of cervical abnormalities to invasive cancer (Behnamfar and Azadehrah, 2015). PAP smear test, used in early diagnosis, is an easily performed, low-cost, harmless test with a high sensitivity and it also decreases treatment burden, morbidity and mortality (Ozdemir and Bilgili, 2010).…”
Section: Investigation Of the Role Of Training Health Volunteers Inmentioning
confidence: 99%